2021
DOI: 10.1039/d1me00120e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular flexibility and head group repulsion on aramid amphiphile self-assembly

Abstract: Strongly interacting amphiphilic molecules self-assemble in water. The flexibility of the amphiphiles and their head group repulsion mediate their nanostructure geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Previously, we confirmed that a bathochromic shift indicates a reduced intermolecular interaction for self-assembled AA nanostructures. 31,40 However, we also confirmed from solution WAXS that the hydrogen bonding network among D-AAs is activated when bathochromic shifts occur at high concentrations (Figure 3b). Hence, we consider that the different packing preference at low and high concentrations is caused by the conformational changes of D-AA, which lead to the shifts and changes in the UV−vis spectra's peak ratios.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previously, we confirmed that a bathochromic shift indicates a reduced intermolecular interaction for self-assembled AA nanostructures. 31,40 However, we also confirmed from solution WAXS that the hydrogen bonding network among D-AAs is activated when bathochromic shifts occur at high concentrations (Figure 3b). Hence, we consider that the different packing preference at low and high concentrations is caused by the conformational changes of D-AA, which lead to the shifts and changes in the UV−vis spectra's peak ratios.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
“…14 However, changes in pH conditions can influence this due to the positively charged surface chemistry. 31 In this study, we maintain the same hydrophilic headgroup of two AAs in order to eliminate any morphological changes that may be related to the headgroup chemistry. Unlike the assembly of CatAAs, the assembly of D-AAs in water shows explicit dependence on the concentration and temperature by conventional transmission electron microscopy (TEM) and cryogenic TEM (cryo-TEM) (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In all cases, we verified that nanoribbon morphologies with consistent dimensions are observed (Figure S7). 43 The site-specific dynamics of each spin-labeled nanoribbon in aqueous suspension were assessed by EPR. The NLSL and CSCA programs were used to fit the spectra with a microscopic order-macroscopic disorder (MOMD) model, which describes the EPR spectra of nitroxyl radicals with local ordering in the slow-motion regime.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Literature values for the β-sheet hydrogen bond and slipped parallel benzene π−π interaction strengths are labeled on the energy axis. 43,44 Nanoribbon schematics adapted from Biophys J., 119 (10), the activation energy of diffusion are relatively low. Nitroxide EPR spectral line shapes are highly sensitive to the intermediate time scale conformational motion characteristic of ordered/viscous liquids and flexible polymer chains and can be influenced by these rotations even if they are of low amplitude.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation